Evaluation of the impact of acidic medications and fluoride-containing mouthwash on the enamel surface using quantitative light-induced fluorescence, microhardness, and scanning electron microscopy: an in vitro study - Saanya Bhasin; Simran Singh; Manuel Sebastian Thomas; Karuna Yarmunja Mahabala; Ramya Shenoy (BMC Oral Health)
Abstract Background Due to their acidic nature, certain medications can have deleterious effects on tooth enamel. Fluoride is a popular method for reversing these effects. Therefore, this study aimed to assess the impact of acidic medications, specifically anti-asthmatic drugs and vitamin C tablets, on enamel surfaces and to investigate the effects of fluoride following drug exposure. Methods An in vitro experimental study was conducted on ninety-six healthy human posterior teeth. Forty-eight samples were tested for surface demineralization via quantitative laser fluorescence (QLF), and the other forty-eight samples were tested for enamel microhardness via a Vickers hardness tester. The samples were divided into six groups: (i) Group DW_NF- samples immersed in distilled water with no fluoride exposure; (ii) Group DW_F- samples immersed in distilled water with intermittent fluoride exposure; (iii) Group VC_NF- samples treated with vitamin C only; (iv) Group VC_F- samples treated with vitamin C and fluoride mouthwash; (v) Group SB_NF- samples exposed to salbutamol inhaler with no fluoride exposure; (vi) Group SB_NF- samples exposed to salbutamol inhaler followed by fluoride exposure. For the evaluation of surface morphology by scanning electron microscopy (SEM), two random samples used for QLF from each group were taken. The Wilcoxon signed-rank test, Kruskal‒Wallis test, and post hoc test were applied as appropriate. The p value was set at 0.05. Results Following exposure to medication, significantly higher QLF values were observed in Group VC_F and Group SB_F than in Group DW-NF (control group) (p = 0.15 and 0.004, respectively). The difference in the QLF values was significantly greater in Group VC_NF than in the control group DW-NF, indicating greater demineralization with acidic medications (p = 0.034). Significant changes in surface microhardness were detected in Group VC_F compared with the control group (p = 0.024). Qualitative analysis of SEM images revealed erosion at the enamel surface in all groups except the control group, with the most prominent erosion in the vitamin C- and fluoride-treated groups (VC_F group). Conclusion This study demonstrated the erosive potential of vitamin C tablets on enamel surfaces. Furthermore, the use of acidic fluoride mouthwash immediately after exposure to acidic medication exacerbates enamel demineralization.